Encyclopedia of Hispanic American literature - Ramirez, Luz Elena; Facts on File, Inc. (New York Facts On File, 2008)
Covers Hispanic-American authors and works that are historically significant or gaining a reputation in today's literary circles. Authors include Isabel Allende, Julia Alvarez, Pat Mora and more.
Electronic reproduction.
Keywords: American literature -- Hispanic American authors -- Encyclopedias; Electronic books